Jihād without apologetics - Van der Krogt, Christopher (Islam and Christian-Muslim relations, 2010)
Accounts of jihād by Western scholars often seek to commend Islam by stressing the spiritual struggle against the self and limiting military jihād to defence. On the basis of this interpretation, drawn from apologetic Muslim sources, writers such as John L. Esposito seek to discredit Muslim terrorists as having ‘hijacked’ Islam and jihād. The paper argues that in order to understand jihād – including terrorism perpetrated by groups such as al-Qa‘ida – it must be recognized as firmly rooted within the heterogeneous tradition that is Islam. Outsiders cannot apply moral criteria for distinguishing between legitimate and illegitimate expressions of Islam; nor should they adopt uncritically the criteria used by more congenial groups of Muslims. Esposito's effort to defend Islam in the face of terrorism results in an inaccurate and inconsistent account of jihād, both past and present. As this example shows, assumptions about the essential goodness of authentic religion impede rather than promote an understanding of the role of religion in the world.